The Influence of the Application of the Demonstration Method on Student Learning Achievement on the Document Storage System Material of the OTKP Department at SMK Negeri 1 Makassar - Andriani Andriani; Haedar Akib; Nasir Nasir (ASHA Publishing, 2024)
In the document storage system material, teaching strategies are needed to support the learning process. Because the material discusses archive systems or documents, types of documents, electronic documents, digital documents and so on. Learning goals will be achieved, if teachers strive to choose the right learning strategy. The learning strategy used by educators in the document storage system material is to use the demonstration method, so that educators will easily apply the material and students will easily understand and apply the theories obtained after the learning process. Choosing the right teaching strategy will increase student learning achievement in terms of skills or expertise. The purpose of the study is to examine the effect of the application of the demonstration method on student learning achievement on the document storage system material of the Department of Office Governance Automation at SMK Negeri 1 Makassar. The approach used is quantitative. Data analysis techniques are descriptive statistics and classical assumption tests. The results of the processing showed: (1) the variable of the application of the demonstration method (X), classified as good. (2) the variable of student learning achievement (Y), reviewed from the student's report card score on the document storage system material which is classified as a very high category with a good score range. (3) The correlation test of product moment is known to have a significant influence and has a moderate relationship. As well as for the simple linear regression test, it shows a positive and significant influence between the variables of the application of the demonstration method (X) on student learning achievement (Y) and the document storage system material at SMK Negeri 1 Makassar